1994
DOI: 10.1177/030098589403100412
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Rhabdomyosarcoma of the Greater Omentum in a Dog

Abstract: Acknowledgementsany staining.This case differs from those described in Suffolk by having unequivocal splenomegaly and severe hemorrhagic enteric involvement consistent with the intestinal form of anthrax.We thank W. Deveer for expertise in photomicroscopy and K. Kuehl and C. Brown for expertise in immunoelectron microscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
2
18
0
1
Order By: Relevance
“…However, there seems to be a trend of similarity with what has been reported in humans, regarding the fact that the majority of rMSs in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx and the jawbone (Seibold, 1974;Sarnelli et al,1994;yanoff et al, 1996;Ginel et al, 2002;, Illanes, 2002;Kobayashi et al, 2004;Suzuki et al, 2006;Bae et al, 2007;Murakami et al, 2010). A few cases of canine rMSs have been reported to arise from striated muscles (Worley and Gorham, 1954;Gonin-Jmaa et al, 1996;Kim et al, 1996;Lascelles et al, 1998;Pérez et al, 1998;Cooper and Valentine, 2002;Machida et al, 2003;Brockus and Myers, 2004;Akkoc et al, 2006;Aupperle et al, 2007;Nakaichi et al, 2007;Chapman et al, 2008;yhee et al, 2008;yamate et al, 2011) and only some of them were further classified.…”
Section: Introductionmentioning
confidence: 64%
“…However, there seems to be a trend of similarity with what has been reported in humans, regarding the fact that the majority of rMSs in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx and the jawbone (Seibold, 1974;Sarnelli et al,1994;yanoff et al, 1996;Ginel et al, 2002;, Illanes, 2002;Kobayashi et al, 2004;Suzuki et al, 2006;Bae et al, 2007;Murakami et al, 2010). A few cases of canine rMSs have been reported to arise from striated muscles (Worley and Gorham, 1954;Gonin-Jmaa et al, 1996;Kim et al, 1996;Lascelles et al, 1998;Pérez et al, 1998;Cooper and Valentine, 2002;Machida et al, 2003;Brockus and Myers, 2004;Akkoc et al, 2006;Aupperle et al, 2007;Nakaichi et al, 2007;Chapman et al, 2008;yhee et al, 2008;yamate et al, 2011) and only some of them were further classified.…”
Section: Introductionmentioning
confidence: 64%
“…To the authors' knowledge, in dogs, four cases of alveolar rhabdomyosarcoma (Seibold Sarnelli et al 1994;Kim et al 1996;Bae et al 2007) have been reported, which occurred in the gingiva, urinary bladder, genital tract, retroperitoneal cavity, left maxillary area and greater omentum, and these cases were confirmed via myoglobin immunohistochemistry. Myogenin is considered as the most critical marker for human rhabdomyosarcoma (Dias et al 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Cross striations can be difficult to demonstrate in poorly differentiated alveolar rhabdomyosarcomas (Sarnelli et al 1994). In this case, we tried to detect cross-striations using PTAH staining; however, no cross-striations were observed in the neoplastic cells, which were considered as poorly differentiated cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many authors reported occasional cases of finding the rhabdomyosarcoma in the heart atrium and chamber (Krotje et al 1990;Gonin-Jmaa et al 1996;Perez et al 1998), perineal area (Ueno et al 2002), parameningeal area (Illanes 2002), tongue (Lascelles et al 1998), gingiva (Kim et al 1996) or greater omentum (Sarnelli et al 1994). Yanoff et al (1996), Block et al (1995) and Hendersen et al (1991) report rhabdomyosarcomas causing tracheal defects.…”
Section: Discussionmentioning
confidence: 99%